Stakeholder perceptions reveal obstacles and opportunities to change lethal methods of protecting bathers from sharks - Atkins, Shanan; Mann-Lang, Judy; Cliff, Geremy; Pillay, Neville; Cantor, Mauricio (My University, 2023)
Bather protection gear—shark nets and baited hooks—is set to catch and kill sharks to protect bathers at popular swimming beaches. This lethal practice contributes to human well-being and safeguards beach tourism, a valuable income-generator. However, it is costly—financially and environmentally. Here we identify obstacles and opportunities to change this lethal method of bather protection in KwaZulu-Natal, South Africa, by assessing the knowledge of people closely involved in this bather-shark conflict. We conducted semi-structured interviews with 29 stakeholders from various organisations—KwaZulu-Natal Sharks Board which manages the gear, three government levels (local, provincial, national), and tourism and conservation organisations—to identify their perceptions about how the gear works, its advantages and disadvantages, and the possibility of changing this method of protecting bathers. Half the interviewees were unaware that the gear intentionally kills sharks. Barriers to changing the 70-year status quo include: mindsets regarding sharks and bather protection in KwaZuluNatal (compared to other places); government officials’ fear of negative consequences of change; politicians prioritising constituents’ short-term well-being; lack of proven alternatives; high cost of potential alternatives; challenging surf conditions; and slow progress of innovation. Opportunities included promising technologies, research and education to rectify misconceptions. We recommend assessing the obstacles and opportunities for change to governance structures (institutions, policies, systems) to implement a programme that accelerates the development and testing of alternatives in KwaZulu-Natal, coupled with a well-designed communication campaign. It is crucial to revisit this long-standing bather protection programme and make it safe for both humans and sharks.
Keywords: Baited drumlines; Conservation; Gillnets; Human-wildlife conflict; Shark attack; Shark bite; Shark nets; SDG-14: Life below water